2010
DOI: 10.3989/scimar.2010.74n4807
|View full text |Cite
|
Sign up to set email alerts
|

Using sagittal otoliths and eye diameter for ecological characterization of deep-sea fish: <i>Aphanopus carbo</i> and <i>A. intermedius</i> from NE Atlantic waters

Abstract: SUMMARY:The sagittal otolith and eye diameter of two sympatric species of the genus Aphanopus, A. carbo and A. intermedius, from North Atlantic waters were investigated. The study objectives were to find morphometric variables of otoliths to identify the two species and relate ecomorphological characters of otolith and eye diameter to the depth distribution of each species. The otoliths of the two species are very similar, although significant differences in shape, otolith height and weight and the sulcus acus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…The S:O ratio and otolith size are related to the hearing capabilities of marine fishes (Gauldie 1988, Montgomery andPankhurst 1997) and ecological factors such as depth distribution, fish mobility and differences in food and spatial niches (Lombarte 1992, Aguirre and Lombarte 1999, Tuset et al 2010. Our results stressed the relevance of the sagittal otolith characteristics to the ecomorphological characteristics, showing otolith shape patterns associated with functional and ecological factors.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The S:O ratio and otolith size are related to the hearing capabilities of marine fishes (Gauldie 1988, Montgomery andPankhurst 1997) and ecological factors such as depth distribution, fish mobility and differences in food and spatial niches (Lombarte 1992, Aguirre and Lombarte 1999, Tuset et al 2010. Our results stressed the relevance of the sagittal otolith characteristics to the ecomorphological characteristics, showing otolith shape patterns associated with functional and ecological factors.…”
Section: Discussionmentioning
confidence: 58%
“…sulcus area, depth of the sulcus, sulcus area:otolith area ratio or shape) vary according to environmental, ontogenetic, phylogenetic and ecological factors (e.g. Nolf 1985, Lombarte 1992, Lombarte and Lleonart 1993, Paxton 2000, Gauldie and Crampton 2002, Volpedo and Echeverria 2003, Lombarte and Cruz 2007, Tuset et al 2010, Reichenbacher et al 2007, Teimori et al 2012. However, it is not known how otolith shape variability affects hearing ability Lu 2000, Popper et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Study indicated strong correlation between otolith width and fish head and total lengths. Many researchers reported similar relationships between otolith and somatic measurements (Lombarte and Lleonart, 1993;Lleonart et al, 2000;Metin and Ilkyaz, 2008;Tuset et al, 2010;Jawad et al, 2011a;Jawad and Al-Mamry, 2012;Valinassab et al, 2012).…”
Section: Discussionmentioning
confidence: 84%
“…In fact, many of these invaders belong to families or genera that are not represented in the native fish fauna of the Mediterranean Sea. Neverthless, ecomorphological characters of otoliths are generally related to the ecological niche that the species occupies (Lombarte 1992, Arellano et al 1995, Aguirre and Lombarte 1999, Lombarte and Popper 2004, Ramcharitar et al 2004, Schulz-Mirbach et al 2008, Colmenero et al 2010, Tuset et al 2010. Thus, the highly differentiated otolithic morphology of Lessepsian species could reflect specific adaptations (Schoener 1974, Motta et al 1995, and hence novel opportunities to thrive in the newly colonized habitat.…”
Section: Discussionmentioning
confidence: 99%